Spatial modelling of eggs of Thrips (Thysanoptera: Frankliniella occidentalis) in husk tomatoes through geostatistical techniques - Jiménez Carrillo, Rocio de los Angeles; Ramírez Dávila, José Francisco; Sánchez Pale, Jesús Ricardo; Salgado Siclán, Martha Lidya; Laguna Cerda, Antonio (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The husk tomato (Physalis ixocarpa Brot.) is a staple food crop of great economic importance in Mexico. However, it is affected by various pests and diseases, such as Thrips (Thysanoptera: Frankliniella occidentalis) and the tomato spotted wilt virus (TSWV) that can cause up to 80% of losses. The scope of the present work was to model the spatial distribution of eggs of Thrips using geostatistical techniques as well as to obtain maps of incidence via krigging. In each of the commercial fields associated to the localities of Luvianos, Jocotitlan e Ixtlahuaca, 121 sampling points were georeferenced through the method of transects across three phenological stages of the crop. The number of Thrips eggs at each sampling point was counted. The results showed a contagious pattern of distribution for the eggs of Thrips, obtaining thus maps provided of several centers of aggregation. Both the Gaussian and spherical models accounted mainly for the obtained semivariograms of the spatial distribution. The infestation by eggs of Thrips is not homogeneously distributed throughout the study area, allowing us to establish strategies and control measures in terms of specific sites of infestation of eggs of Thrips.